Oral Liquid Potassium Chloride Dosing Pathway in a Tertiary Care Veteran Affairs Academic Medical Center. Issue 1 (March 2020) - Benge, Cassandra D.; Burka, Abigail T.
Abstract : Hypokalemia, defined as a serum potassium (K + ) concentration of <3.5 mEq/L, is an electrolyte imbalance commonly found in hospitalized patients. Hypokalemia is associated with potentially severe complications, including arrhythmias, which necessitate careful monitoring and repletion with potassium. In the inpatient setting, serum K + may be repleted via intravenous or oral routes, with oral administration preferred. Potassium chloride (KCl) for oral administration is widely available in both immediate as well as an extended release formulations. Immediate release liquid KCl is optimal for inpatient use since it demonstrates rapid absorption and subsequent increase in serum K + levels. However, acquisition costs for unit dose oral liquid KCl have prompted some institutions to implement guidance for appropriate use of KCl oral liquid. In this article, we describe the creation of a clinical pathway for ordering of oral immediate release KCl for inpatients at a tertiary Veterans Affairs Academic Medical Center.